THE RELATIONSHIP BETWEEN FINANCIAL LITERACY, PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND IMPULSIVE BUYING BEHAVIOR ON PAYLATER USAGE - Mikael, Jeremy
The massive growth of digital payment alternatives in Indonesia is inevitable as customers demand an easier and more efficient business process, especially when shopping in e-commerce. To attract more customer, many e-commerce platforms adopt innovative payment alternative to provide more seamless and convenient process to its customer, one of these alternatives is paylater. The mass adoption of paylater is a result of benefits offered, a more accessibility and an easier requirement to request consumer loan compared to credit cards. However, the ease and usefulness provided by paylater may lead to some potential problems related to excessive loan bill and debt which damages the user credit and a potential bad debt for e-commerce platforms. Personal financial well-being may also be damaged as paylater usage tends to trigger impulsive buying behavior. Therefore, improving financial literacy to make a well-informed financial decision can be considered in preventing these problems.